Neuroprotective Effects of Collagen-Glycosaminoglycan Matrix Implantation following Surgical Brain Injury - Jia-Hui Chen; Wei-Cherng Hsu; Kuo-Feng Huang; Chih-Huang Hung (Mediators of Inflammation)
Background. Neurological deficits following neurosurgical procedures are inevitable; however, there are still no effective clinical treatments. Earlier reports revealed that collagen-glycosaminoglycan (CG) matrix implantation promotes angiogenesis, neurogenesis, and functional recovery following surgical brain injury (SBI). The present study was conducted to further examine the potential neuroprotective effects of collagen-glycosaminoglycan (CG) matrix implantation following neurosurgery. Methods. CG implantation was performed in the lesion cavity created by surgical trauma. The Sprague-Dawley rat model of SBI was used as established in the previous study by the author. The rats were divided into three groups as follows: (1) sham (SHAM), (2) surgery-induced lesion cavity (L), and (3) CG matrix implantation following surgery-induced lesion cavity (L+CG). Proinflammatory (tumor necrosis factor-alpha (TNF-α), interleukin-6 (IL-6), and NF-κB (nuclear factor kappa-light-chain-enhancer of activated B cells)) and anti-inflammatory (IL-10 and granulocyte-macrophage colony-stimulating factor (GMCSF)) cytokine expression was evaluated by enzyme-linked immunosorbent assays. Microglial activation was evaluated by immunohistochemistry, and the neuroprotective effect of CG matrix implantation was evaluated by an immunohistochemical study of microglia ED-1 and IBA-1 (activated microglia) and myeloperoxidase (MPO) and by the analysis of IL-6, IL-10, TNF-α, NF-κB, and GMCSF cytokine levels. Apoptosis was also assessed using a TUNEL assay. Results. The results showed that CG matrix implantation following surgically induced lesions significantly decreased the density of ED-1, IBA-1, and MPO (activated microglia). The tissue concentration of proinflammatory cytokines, such as TNF-α, IL-6, and NF-κB was significantly decreased. Conversely, the anti-inflammatory cytokines GMCSF and IL-10 were significantly increased. Conclusions. Implantation of the CG matrix following SBI has neuroprotective effects, including the suppression of microglial activation and the production of inflammatory-related cytokines.